Short-term effects of escitalopram on regional brain function in first-episode drug-naive patients with major depressive disorder assessed by resting-state functional magnetic resonance imaging - Wang, L.; Li, K.; Zhang, Q.; Zeng, Y.; Dai, W.; Su, Y.; Wang, G.; Tan, Y.; Jin, Z.; Yu, X.; Si, T. (Psychological medicine, 2014)
Most knowledge regarding the effects of antidepressant drugs is at the receptor level, distal from the nervous system effects that mediate their clinical efficacy. Using functional magnetic resonance imaging (fMRI), this study investigated the effects of escitalopram, a selective serotonin reuptake inhibitor (SSRI), on resting-state brain function in patients with major depressive disorder (MDD). Fourteen first-episode drug-naive MDD patients completed two fMRI scans before and after 8 weeks of escitalopram therapy. Scans were also acquired in 14 matched healthy subjects. Data were analyzed using the regional homogeneity (ReHo) approach. Compared to controls, MDD patients before treatment demonstrated decreased ReHo in the frontal (right superior frontal gyrus), temporal (left middle and right inferior temporal gyri), parietal (right precuneus) and occipital (left superior occipital gyrus and right cuneus) cortices, and increased ReHo in the left dorsal medial prefrontal gyrus and left anterior lobe of the cerebellum. Compared to the unmedicated state, ReHo in the patients after treatment was decreased in the left dorsal medial prefrontal gyrus, the right insula and the bilateral thalamus, and increased in the right superior frontal gyrus. Compared to controls, patients after treatment displayed a ReHo decrease in the right precuneus and a ReHo increase in the left anterior lobe of the cerebellum. Successful treatment with escitalopram may be associated with modulation of resting-state brain activity in regions within the fronto-limbic circuit. This study provides new insight into the effects of antidepressants on functional brain systems in MDD.